(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Intending to study the “Reproductive Health among women of Scheduled Caste” in Bihar in general and Patna in particular a cross sectional study was conducted among the scheduled caste (SC) peoplefamily in and around Patna District in order to understand their reproductive health profile. The age at marriage, age at 1st conception, morality rate of new-born, morality of mother at the time of giving birth, etc. were studied. The educational Economic background of the individualFamily whole group was also studied.To elaborate further, we can state that a survey was conducted for studying the reproductive (Darwinian) fitness in the four prominent endogamous Scheduled Caste populations of the district of Patna (Bihar), namely, the Dusadhs, the Chamars, the Pasis and the Musahars, were surveyed. The data were collected through door-to-door survey among a random representative sample of the subjects belonging to the same socio-economic status. A proforma of questionnaire was used to measure the reproductive fitness of the members.It was also found that the groupcaste which had relatively better educational, Social Economical status had better reproductive health profile as adjudged by contraceptive used, place of child deliveries, antenatal care and consumption of vitaminiron pills during pregnancy.